2022
DOI: 10.1111/cas.15557
|View full text |Cite
|
Sign up to set email alerts
|

miR‐92a‐3p encapsulated in bone metastatic mammary tumor cell–derived extracellular vesicles modulates mature osteoclast longevity

Abstract: Aberrant osteoclast formation and activation are the hallmarks of osteolytic metastasis. Extracellular vesicles (EVs), released from bone metastatic tumor cells, play a pivotal role in the progression of osteolytic lesions. However, the mechanisms through which tumor cell–derived EVs regulate osteoclast differentiation and function have not been fully elucidated. In this study, we found that 4T1 bone metastatic mouse mammary tumor cell–derived EVs (4T1‐EVs) are taken up by mouse bone marrow macrophages to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the molecular signature found in this study, hsa-miR-92a-3p has been described as a promoter of cell proliferation in breast cancer cells by modulating Krüppel-like transcription factors (KLFs) [28]. Regarding the inclusion of this miRNA in EVs, a recent study by Uehara et al uses a mouse model to demonstrate that miRNA-92a-3p contained in EVs promotes osteolytic metastasis by directly blocking PTEN in mature osteoclasts [29]. As a potential biomarker in gastric cancer, hsa-miR-92a-3p was found to be overexpressed in plasma in a cohort of 160 patients with gastric cancer and validated in independent cohorts as an early diagnostic marker.…”
Section: Exosomal Mirnas In Gastric Cancermentioning
confidence: 70%
“…In the molecular signature found in this study, hsa-miR-92a-3p has been described as a promoter of cell proliferation in breast cancer cells by modulating Krüppel-like transcription factors (KLFs) [28]. Regarding the inclusion of this miRNA in EVs, a recent study by Uehara et al uses a mouse model to demonstrate that miRNA-92a-3p contained in EVs promotes osteolytic metastasis by directly blocking PTEN in mature osteoclasts [29]. As a potential biomarker in gastric cancer, hsa-miR-92a-3p was found to be overexpressed in plasma in a cohort of 160 patients with gastric cancer and validated in independent cohorts as an early diagnostic marker.…”
Section: Exosomal Mirnas In Gastric Cancermentioning
confidence: 70%
“…For example, Chen et al found that after interacting with integrins, intercellular adhesion molecule 1 caused tumor cells to undergo EMT via TGF-β/SMAD signaling, after which the cells’ mesenchymal properties facilitated tumor cell metastasis through blood circulation [85] . Furthermore, because BC cells’ exosomes disrupt bone remodeling in the BM process, they may effectively serve as drug carriers for treating MBCB [86] , [87] . Therefore, it is not surprising that “bone remodeling” continues to be a keyword in the field of MBCB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the higher presence of miR‐19a‐3p‐loaded EVs is likely to be responsible for the bone destruction and osteopenia observed in an osteosarcoma mice model (Luo et al, 2021). Similarly, exosomes obtained from both osteoblastic and osteoclastic prostate cancer cells, and bone metastatic mammary tumor cells transporting miR‐92a‐1‐5p and miR‐92a‐3p promote osteoclast differentiation and favor mature osteoclasts survival by reducing type I collagen expression and via the Akt signaling pathway, respectively (Uehara et al, 2022; Yu et al, 2021). In this way, the treatment of osteoclast precursors such as Raw 264.7 cells, resulted in an increased osteoclastogenesis and bone resorption in vitro, after the administration of 100 ng/mL of miR‐92a‐3p‐loaded EVs (Uehara et al, 2022).…”
Section: Natural Nanoparticlesmentioning
confidence: 99%
“…Similarly, exosomes obtained from both osteoblastic and osteoclastic prostate cancer cells, and bone metastatic mammary tumor cells transporting miR‐92a‐1‐5p and miR‐92a‐3p promote osteoclast differentiation and favor mature osteoclasts survival by reducing type I collagen expression and via the Akt signaling pathway, respectively (Uehara et al, 2022; Yu et al, 2021). In this way, the treatment of osteoclast precursors such as Raw 264.7 cells, resulted in an increased osteoclastogenesis and bone resorption in vitro, after the administration of 100 ng/mL of miR‐92a‐3p‐loaded EVs (Uehara et al, 2022). Similarly, the treatment of Raw 264.7 cells or bone marrow macrophages with 20 μg/mL of prostate cancer‐cell derived exosomes containing miR‐92a‐1‐5p for 6 days have found to promote osteoclast differentiation in vitro (Yu et al, 2021).…”
Section: Natural Nanoparticlesmentioning
confidence: 99%